Analisis Struktur dan Komposisi Vegetasi Tumbuhan Di Taman Hutan Raya Raden Soerjo Prigen Pasuruan - Nia Sylviana Sari; Samsun Hadi; Rr. Eko Susetyarini (ULIN: Jurnal Hutan Tropis, 2021)
Long drought and uncontrolled human activities resulted in R. Soerjo Prigen Pasuruan Grand Forest Park experiencing fire. Adverse impacts on vegetation can result in vegetation death. Damage caused by fire to vegetation can lead to succession which can be seen from the composition and structure of forest vegetation. The purpose of this study was to determine the effect of environmental parameters, structure and composition of plant vegetation in Tahura R. Soerjo, which were used as a learning resource for biology. This study used a purposive sampling technique. The method used is a combination of paths and checkered lines. The data analysis technique used is the Importance Value Index (INP), the dominance index, the diversity index, the wealth index, and the evenness index. The results showed that the identification of plant vegetation diversity was found as many as 33 species from 17 families that came from 3 divisions. The highest INP was found at the seedling level. The value of the dominance index is less than 1. The results show that the value of the density index is low, because it has a value of <3.5. The evenness value is at a high value, except at the tree level.